Model Kewirausahaan Sosial di Lembaga Agriculture Entrepreneur Clinics - Yuliska, Yuliska (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2018)
Entrepreneur activities are very important, not only become tools for increasingly individual life quality but also to improve state qualities. For the reason, a country must be having entrepreneurship to very much in society. Hence, as an organization of mobility form entrepreneur motivation, Agriculture Entrepreneur Clinics (AEC) has had the commitment to improving the quality of people. With the field research, this article aims to describe of concept, implementation, and result who social entrepreneur in this institution of AEC. The result of research is showing that the concept of social entrepreneurship in the institution of AEC conducted with the way of revolving and advantageous between institution AEC and peasant in simultaneously. Meanwhile, in implementation is conducting of the activities just like shared rice excellent from the result of researching discovery, conducted of new training methods for the ways of plant, coaching, and buying rice for harvest farmers who then sold by institution AEC. Social entrepreneurship in the institution AEC is not only improving for management but also increasingly for society.Pentingnya berwirausaha tidak hanya menjadi alat untuk meningkatkan kualitas hidup secara individu, namun juga untuk meningkatkan kualitas negara. Atas dasar inilah sebuah negara harus memiliki pengusaha yang banyak. Dengan demikian, sebagai lembaga yang bergerak dalam bidang motivasi wirausaha, lembaga Agriculture Entrepreneur Clinics (AEC) memiliki komitmen untuk meningkatkan taraf hidup masyarakat. Melalui penelitian lapangan, maka artikel ini hendak mendeskripsikan konsep, implementasi dan hasil yang dicapai dalam berwirausaha sosial di lembaga AEC. Hasil penelitian menunjukkan bahwa konsep kewirausahaan sosial di lembaga AEC dilakukan dengan cara berputar dan sama-sama menguntungkan antara lembaga AEC dengan petani binaannya. Implementasinya, yaitu dengan melakukan kegiatan seperti membagikan padi unggul hasil temuan lembaga, melakukan pelatihan metode tanam terbaru, melakukan pendampingan, dan membeli padi hasil panen petani  yang kemudian dijual dalam bentuk beras oleh lembaga AEC.  Kewirausahaan sosial di lembaga AEC ini tidak hanya menguntungkan bagi lembaga saja, namun juga menguntungkan bagi masyarakat.